2014
DOI: 10.3906/muh-1401-13
|View full text |Cite
|
Sign up to set email alerts
|

DEM resolution and stream delineation threshold effects on the results of geomorphologic-based rainfall runoff models

Abstract: Digital elevation model (DEM) resolution and the assigned threshold for river network delineation affect the results of rainfall-runoff models. In this study, the effects of these 2 issues on the extracted geomorphologic parameters of watersheds and the performance of a kinematic wave based model, called KW-GIUH, are investigated. The results show that by decreasing the DEM resolution at fixed thresholds, parameters such as subbasin mean slope and the number of streams decrease and the area of the i th order s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the last two decades, the automatic identification of drainage networks and drainage basins from DEMs has become increasingly popular through the use of various GIS software packages (García and Camarasa, 1999;Turcotte et al, 2000;Robl et al, 2008;Bahrami, 2013;Ariza-Villaverde et al, 2015;Gürbüz et al, 2015). Several studies highlighted the effect of DEM resolution on the accuracy of hydrologic modelling and associated drainage networks (Garbrecht and Martz, 1994;Zhang and Montgomery, 1994;Cotter et al, 2003;Chaubey et al, 2005;Hosseinzadeh, 2011;Sharma et al, 2011;Azizian and Shokoohi, 2014). DEMs of different resolutions have the potential to significantly affect watershed and stream network delineation.…”
Section: Delineation Of Drainage Networkmentioning
confidence: 99%
“…In the last two decades, the automatic identification of drainage networks and drainage basins from DEMs has become increasingly popular through the use of various GIS software packages (García and Camarasa, 1999;Turcotte et al, 2000;Robl et al, 2008;Bahrami, 2013;Ariza-Villaverde et al, 2015;Gürbüz et al, 2015). Several studies highlighted the effect of DEM resolution on the accuracy of hydrologic modelling and associated drainage networks (Garbrecht and Martz, 1994;Zhang and Montgomery, 1994;Cotter et al, 2003;Chaubey et al, 2005;Hosseinzadeh, 2011;Sharma et al, 2011;Azizian and Shokoohi, 2014). DEMs of different resolutions have the potential to significantly affect watershed and stream network delineation.…”
Section: Delineation Of Drainage Networkmentioning
confidence: 99%
“…To evaluate the model response for the different soil representations, the model should have a sufficient number of sub-basins. We did not set equal threshold areas for both of the watersheds (Figure 4a), because the required threshold area for the small watershed creates too many sub-basins for the large watershed that would need smart computer architecture [48]. The digitized stream networks were used to improve hydrographic segmentation and sub-watershed boundary delineation.…”
Section: Model Setup and Calibrationmentioning
confidence: 99%
“…Besides, he showed that the accuracy of computed T c is largely controlled by the accuracy of roughness coefficient. Azizian and Shokoohi (2014;2015a) investigated the scale effects and streams delineation threshold on geomorphological parameters on the performance of KW-GIUH model and found that the coefficients of variation of river length, river mean slope and time of concentration is about 18.8, 19.3 and 21%. There are several statistical and mathematical methods that can be used to propagate input uncertainties through the model into output uncertainties, of which the First-Order-Analysis (FOA) proposed by Tung and Mays (1981) is one of the most common methods.…”
Section: Introductionmentioning
confidence: 99%